Implementasi Sistem Informasi Showroom Mobil (SISMOB) dengan Pemrograman Berbasis Objek (Studi Kasus: UD. Tomaru Oto) - Muhammad Afif Fakhri; Ismiarta Aknuranda; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
UD. Tomaru Oto is selling cars, both new and used. In running their business, UD. Tomaru Oto still do it manually. The Owner of UD. Tomaru Oto records all transactions manually on the books of receipts, so if the books of receipts are lost, then all the transaction data are getting lost too. In addition, status of the customer is not recorded and only rely on the owner's memories, so often the owner forgot whether the customers have paid off the transactions or still not pay off the transactions. Another problem is the absence of recapitulation of income and expenditure per month. According from those problems, it needs an information system of car showroom (SISMOB) on UD. Tomaru Oto. The objectives of this research include designing the implementation of SISMOB, the implementation of SISMOB using object oriented programming (OOP), and the testing of SISMOB using blackbox and whitebox method. The design for implementation SISMOB is adapted to the COdeIgniter Framework. The result of implementation SISMOB is the SISMOB application. The testing of SISMOB using blackbox method is for testing all of the uses cases and the whitebox method only testing three uses cases. The result of testing SISMOB using blackbox method is all running in accordance with the uses cases specification that already designing. The result of the test using whitebox method produce cyclomatic complexity and independent path, which all of the independent paths have been passed at least once.